Temporary Workers in Canada: A National Perspective - Trumper, Ricardo; Wong, Lloyd L. (Canadian Issues, 2010)
Temporary workers come to Canada under the auspices of the Immigration and Refugee Protection Act, and specifically, the Temporary Foreign Worker Program (TFWP). They are unfree in the sense that they are unable to circulate within the labour market due to legal constraints. This article contextualizes Canada's TFWP within the global political economy in terms of flexible labour, racialization and genderization. Temporary workers are flexible; they provide "j ust- in- time" labour to meet what are perceived to be shortages of workers in the labour market. While this labour is flexible from the point of view of the employer, it is "precarious" from the vantage point of the worker. Employers use the TFWP to have direct power over who immigrates to Canada, slowly eroding the goals of meritocratic fairness that have supported Canadian purported efforts to make (im)migration an impartial process. Although global political economy is a good starting point for framing temporary labour in Canada, it is not sufficient. Since Confederation, Canada has always had some type of temporary worker process. The ideal of creating a British settler community was Canada's original nation-building goal, but the reality was that the Canadian capitalist class preferred temporary workers for agricultural and industrial work, infrastructure and railway construction, and domestic work; Asian and Southern and Eastern European males filled many of these positions. In railway construction and mining, for example, there were racialized labour segments with distinct groups of workers: "Whites" in higher paid and "safe" occupations, and "foreigners" who were in lower-paid and dangerous jobs (Vosko 2000) - the latter group often being hired as temporary workers. There is also a long history in Canada of foreign domestic workers serving middle- and upper-class families dating back to the late 180Os and early 1900s. Formally, under the strict logic of the immigration legislation that vows to bring to Canada the "best and the brightest" (or the very skilled), the "unskilled" workers should not be allowed to stay in Canada. However, as the work of researchers at Brandon University points out, after six months, many temporary workers arriving in Manitoba who labour in unskilled or semi-skilled occupations apply to the Provincial Nominee Program (PNP). In this sense, temporary migrants become "transitional" foreign workers (Annis 2008, Bucklaschuk 2008). Unfree labour becomes both a vehicle for a probationary period for migrants and for a new style of immigration that is driven by employers rather than the state, allowing for unsupervised racial, geographical, or gender bias.
Keywords: Foreign labor; Humanities: Comprehensive Works; Immigration policy; LABOR market; Social Sciences: Comprehensive Works; Studies; Temporary employment